EFEKTIVITAS PENGGUNAAN LEACHET HASIL PENGURAIAN SAMPAH DALAM PROSES BIODEGRADASI LIMBAH BATIK - Mulasari, Surahma asti (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2012)
Background : Treatment of textile waste industry, including batik can be implemented with a biodegradation. Biodegradation by bacteria carried either aerobic or anaerob. The bacteria are widely found in nature. On the other hand, the presence of bacteria in nature also function to decompose the waste. Own waste as a potential waste in the community. The use of environmental biotechnology is possible to simultaneously address the environmental pollution caused by waste and garbage batik. The purpose of this study was to investigate to find out the difference amount of in degrading microbial in leachet, the difference in content of organic C, N, and P in leachet as a nutrient for degrading microbial growth, the effectiveness of the use leachet biodegradation in the process of batik , and to determine the effectiveness of different leachet in the biodegradation process of batik waste management.Methods : This was quantitative study with laboratory test to determine differences in the effectiveness of the use of leachet.Results : The content contained microbs / bacteria so that the possibility of a biological process can be implemented. There wave had of N, P, K nutrients in leachet for bacteria, waste pollution parameters decreased but didnât significantly improve the quality of batik waste.Conclusion : There was no significant reduction the quality of batik waste.Key words : waste, leachet, garbage, batik.